2015
DOI: 10.1039/c4ra17134a
|View full text |Cite
|
Sign up to set email alerts
|

Electron induced ionisation of C3 to C6 ethanoates

Abstract: 5The present article reports calculation of electron impact total ionisation cross sections for C 3 to C 6 ethanoates for the energy range from ionisation threshold of the target to 5000 eV. The spherical complex optical potential and complex scattering potential ionisation contribution methods are employed to calculate the cross sections. The results presented here show consistent variation with previous measurements and theoretical values, wherever available. The dependence of isomeric effect on the ionisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…The ratio of Q ion to Q inel (R p ) at the peak (Eq. (7)) is found to be between 70 and 80% as reported by Turner et al [27] and Karwasz et al [28] This was also confirmed by the authors [16][17][18][19]. This causes an uncertainty which can be determined by calculating the cross section at the peak using R p = 0.60, 0.65, 0.7, 0.75 and 0.8.…”
Section: Theoretical Methodologysupporting
confidence: 91%
See 4 more Smart Citations
“…The ratio of Q ion to Q inel (R p ) at the peak (Eq. (7)) is found to be between 70 and 80% as reported by Turner et al [27] and Karwasz et al [28] This was also confirmed by the authors [16][17][18][19]. This causes an uncertainty which can be determined by calculating the cross section at the peak using R p = 0.60, 0.65, 0.7, 0.75 and 0.8.…”
Section: Theoretical Methodologysupporting
confidence: 91%
“…The correlation between the maximum of ionization cross section versus square root of the ratio of polarizability to ionization potential of methyl and ethyl formates is plotted in Fig. 7 along with aldehyde, ketone, cycloalkane, and methyl and ethyl acetate from previously reported work [18,19]. The same correlation plot is employed to compute the polarizabilities of C 4 to C 6 formates, since polarizability volumes for these molecules are not available in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations